DASAR PERTIMBANGAN HUKUM PUTUSAN HAKIM MAHKAMAH KONSTITUSI TERKAIT PELAKSANAAN PILEG DAN PILPRES TAHUN 2014 DAN 2019 - Desinta Dwi Rapita (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract Legal consideration base of judge becomes a determinant or basis for a judgement. This research aims to describe and analize appropriateness of legal consideration base of judge in making Verdict of constitutional court Number 14/PUU-XI/2013 in connection to implementation of Legislative and Presidential Election in accordance with pure legal consideration based on possitive law or by legal consideration outside the possitive law. Further, describe and analize legal implication appeared from Verdict of constitutional court Number 14/PUU-XI/2013 on implementation of Legislative and Presidential Election 2014 and 2019. This research is type of legal research using normative point of view. Research approach used statue approach and conceptual approach. Type of legal material used is primary legal material and sekondary legal material. Result of research shows that legal consideration base of constitutional judge in decision of constitutional court Number 14/PUU-XI/2013 in accordance with pure legal consideration based on possitive law and also based on legal consideration outside the positive law. Decision of constitutional court Number 14/PUU-XI/2013 has legal implication on general election of 2014 and also general election of 2019. legal implication of the judement on implementation of general election in 2014 is that Legislative and Presidential Election is not held simultanously and according to the general election legislation, that is Law No. 42 of 2008 on Election of President and Vice President. While on general election of 2019 it will be held simultanously in accordance with the new legislation made by the legislator. Key word: decision of constitutional court, legal consideration base, simultanous general election Abstrak Dasar pertimbangan hukum oleh hakim menjadi penentu atau dasar sebuah putusan. Tujuan penelitian ialah untuk mendeskripsikan dan menganalisis dasar pertimbangan hukum hakim dalam putusan MK No. 14/PUU-XI/2013 dan mengetahui implikasi hukum putusan MK No. 14/PUU-Xi/2013. Penelitian ini merupakan jenis penilitian hukum dengan pendekatan penelitian yang digunakan ialah pendekatan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Hasil penelitian menunjukkan bahwa dasar pertimbangan hukum hakim konstitusi dalam Putusan Mahkamah Konstitusi Nomor 14/PUU-XI/2013 sesuai dengan pertimbangan hukum murni berdasarkan hukum positif dan juga didasarkan pada pertimbangan hukum di luar hukum positif. Implikasi hukum Putusan Mahkamah Konstitusi Nomor 14/PUU-XI/2013 terhadap pemilu tahun 2014 dan juga pemilu tahun 2019 ialah bahwa Pileg dan Pilpres tetap dilaksanakan tidak serentak dan sesuai dengan ketentuan undang-undang Pemilu, yaitu UU No. 42 Tahun 2008 tentang Pemilihan Presiden dan Wakil Presiden. Sedangkan pada Pemilu 2019 nanti Pemilu akan dilaksanakan serentak sesuai dengan ketentuan perundang-undangan baru atau hasil amandemen yang dibuat oleh legislator. Kata kunci: Putusan Mahkamah Konstitusi, dasar pertimbangan hukum, Pemilu serentak